Pengaruh Keragaman Menu, Kualitas Pelayanan Kualitas Produk, Dan Harga Terhadap Kepuasan Konsumen Pada Rumah Makan Bebek H. Slamet Kota Kediri - Ake Akbar Mahe; Bambang Suwarsono; Umi Nadhiro (Universitas 45 Surabaya, 2023)
This study aims to determine the effect of menu diversity, service quality, product quality, and price on consumer satisfaction. The research method used is a quantitative method with a descriptive approach. Data collection in this study was carried out by distributing questionnaires to consumers at Bebek H. Slamet Restaurant in Kediri City and calculated using the SPSS Version 25 application. Data analysis techniques used included validity testing, reliability testing, classical assumption testing, and multiple linear regression testing. In the Validity Test it is known that all question items (X1, X2, X3, X4, and Y) have a total correlation of 0.185 > 0.05, so that each variable is declared valid. Then in the Reliability Test it is known that the Cronbach Alpha value results are > 0.60 so that the indicators for each question are declared reliable. In the t test it is known that all items have positive values and <0.05 so that all items (Menu Diversity, Service Quality, Product Quality, and Price) have an effect on Consumer Satisfaction. Then in the F Test it is known that the value of Sig. for all items together it is 0.002 < 0.05 and the Fcount value is 5.635 > 2.02, it can be concluded that the variables of Menu Diversity, Service Quality, Product Quality, and Price have a simultaneous effect on Consumer Satisfaction.